1989
DOI: 10.1159/000185645
|View full text |Cite
|
Sign up to set email alerts
|

Serum Tamm-Horsfall Protein Levels in Childhood: Relationship with Age and Glomerular Filtration Rate

Abstract: Serum Tamm-Horsfall protein (THP) levels were measured in 157 infants and children, 46 cord blood samples and 75 adults using an enzyme-linked immunosorbent assay. THP levels increased significantly across the age groups, suggesting a positive relationship with age. There was a strong positive relationship between serum THP and estimated glomerular filtration rate among children with chronic renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…These levels were consistent with those reported by Avis [5] and Dawnay and C'attell [12]. Alfaham et al [13] re cently reported that serum THGP levels were lowered, especially in younger infants. In our study, there was no significant relationship between serum THGP levels and age.…”
Section: Discussionsupporting
confidence: 90%
“…These levels were consistent with those reported by Avis [5] and Dawnay and C'attell [12]. Alfaham et al [13] re cently reported that serum THGP levels were lowered, especially in younger infants. In our study, there was no significant relationship between serum THGP levels and age.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, an absolute increase in Scr might vary substantially in children and was not suitable for diagnosing AKI in younger ages [ 47 ]. The serum UMOD levels also increased significantly during growth [ 48 ], but with the elucidated subgroup difference in different age groups. Therefore, uUMOD is more valuable and helpful to predict AKI of children, as well as a more easy to accessible and non-invasive process than serum UMOD for children.…”
Section: Discussionmentioning
confidence: 99%
“…Both indirect as well as direct ELISA setups have been reported for urinary [5,[97][98][99][100][101] and serum [91,102,103] measurements. In the 1990s, Syn elisa THP immunoassay was available from Elias Medizintechnik GmbH (Freiburg, Germany; which later became Elias/Pharmacia & Upjohn), but its production was eventually discontinued.…”
Section: Biochemical Analysismentioning
confidence: 99%